Effect of IL-1β and IL-1RN polymorphisms in carcinogenesis of the gastric mucosa in patients infected with Helicobacter pylori in Algeria. Issue 1 (1st January 2016) - Drici, Amine El-Mokhtar; Moulessehoul, Soraya; Tifrit, Abdelkarim; Diaf, Mustapha; Turki, Douidi Kara; Bachir, Meryem; Tou, Abdenacer
Abstract : Background: Infection with Helicobacter pylori is considered a potential risk of developing gastric cancer in association with contributing host genetic factor. IL-1β and IL-1RN polymorphisms appear to maintain and promote Helicobacter pylori infection and to stimulate neoplastic growth of the gastric mucosa. Objective and methods: In order to elucidate the effect of these polymorphisms in combination with gastric cancer in a population from northwestern Algeria, a case-control study was carried out on 79 patients infected with H. pylori with chronic atrophic gastritis and/or gastric carcinoma, and 32 subjects were recruited as case-control. IL-1β-31 bi-allelic and IL-1β-511 bi-allelic polymorphisms and IL-1RN penta-allelic were genotyped. Results: IL-1β-31C was associated with an increased risk of developing gastric carcinoma (OR=4.614 [1.43−14.81], p= 0.01). However, IL-1RN2 heterozygous allele type was significantly associated with chronic atrophic gastritis (OR=4.2 [1.23−3.61], p= 0.022). IL-1β-511T was associated with an increased risk of development of chronic atrophic gastritis (OR=4.286 [1.54−11.89], p= 0.005). Conclusion: IL-1β and IL-1RN polymorphisms associated with H. pylori infection contribute to the development of chronic atrophic gastritis and gastric carcinomas in an Algerian population. The alleles IL-1β-31C and IL-1RN were associated with an increased risk of developing gastric carcinoma, and IL-1β-511T with an increased risk of developing chronic atrophic gastritis with no significant association of developing gastric carcinoma.